RESULTS OF EXPERIMENTAL TESTS OF CATEGORY M3BUS BRAKING EFFICIENCY IN APPLICATION TO EXPERT PRACTICE (Academic journal Industrial Machine Building Civil Engineering, 2017)
This research is aimed at study of braking efficiency of bus that is equipped with an anti-blocking pneumatic braking system. The braking efficiency test results, obtained in this research, are different from those used by  car expert specialists in a car accident investigation. Therefore, practical recommendations on usage of those test results in the expert practice are given. Keyword:bus, brake tests, slow, expertise, traffic accident.